Indigènes, Africains et Afrodescendants dans l’œuvre de Frans Post - Bartira Ferraz Barbosa; Natália Moragas (Caravelle)
This article concerns the representation of Indigenous People, African and African Descendants in the work of Frans Post, a xviith century Dutch painter who lived in Recife. The paintings, drawings and engravings we selected for this study refer to different periods of Post’s work. They represent the activities of free men and women, of slaves or freed slaves in the Luso-Dutch colonial world in Brazil. They are characters that were recreated in landscapes evoking the nature of the Northeast coast with buildings such as fortifications, sugar mills, villages and roads. The article engages with the history of cultural interactions, of visual arts and of the imagery in graphic representations. At the same time, it concerns the construction of the historical heritage that was left to us by the colonization process and its inevitable cross influences.